A systematic map of responses to climate impacts in urban Africa - NB Hunter; MA North; DC Roberts; R Slotow (Environmental Research Letters, 2020)
Over time African cities and their residents have responded to climate impacts in increasingly creative ways, based on local knowledge and available resources. Overviews of adaptation policy, plans and actions have largely been lacking for Africa, particularly at the local, city level. We applied a systematic map to assess what the human responses to climate impacts are in African cities, noting the climate drivers of these actions, the range of responses, where they have taken place, and who the actors are. Standardized, pre-selected search terms were used to systematically search peer-reviewed and grey literature, using Web of Science, Scopus, and Google. Publications were screened based on pre-approved inclusion criteria, and actions described in included articles were coded using categories from key conceptual framing papers on climate change adaptation. Of 2 042 peer-reviewed and 60 grey-literature publications, 252 underwent full-text screening, with 121 included for coding. We recorded 1 504 actions, taking place in 41 cities from 21 African countries, in response to various climate drivers. Anticipatory and reactive actions were taken by actors, from individuals to international agencies, and we highlighted successful adaptations, those taking advantage of climate impacts, and maladaptive actions. Combinations of climatic and non-climatic stimuli induced adaptive responses, which were frequently based on local knowledge, and provided a base upon which government action could build. Residents of informal settlements had less adaptive capacity than those in formal settlements, and government action could build their resilience. Since development is affected by climate impacts, climate change information should be integrated into development programmes.